Rozumienie przez dzieci 6-, 7- i 8-letnie występowania wody w gruncie - Jan Amos Jelinek (Problemy Wczesnej Edukacji)
Groundwater is out of direct observation. Their presence can be inferred from the observation of water disappearing in puddles, wells and lakes. The article presents a childlike explanation of these three phenomena. The study covered 50 children aged from 6 to 8 years. The obtained explanations have been categorised into mental models and arranged in relation to the degree of approximation to the scientific explanation. The research showed that children do not refer to groundwater when explaining the phenomenon of water disappearance in puddles and the origin of water in a well and lake. They are aware of the existence of water in the ground, but their cognitive horizon is limited to a deliberate explanation of the phenomena of water origin (e.g. water from rain immediately penetrates a well). The research has shown that children lack experience in preserving water in the ground and conclusions for pedagogical practice have been presented.